2019
DOI: 10.1007/s13187-019-01540-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Patient Education Class to Enhance Knowledge about Lung Cancer Screening: a Quality Improvement Evaluation

Abstract: Background.-Best practices to facilitate high-quality shared decision-making for lung cancer screening (LCS) are not well established. In our LCS program, patients are first referred to attend a free group education class on LCS, taught by designated clinician specialists, before a personal shared decision-making visit is scheduled.Objective.-To evaluate class effectiveness in enhancing patient knowledge and shared decisionmaking about LCS.Methods.-For quality improvement purposes, participants were asked to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
0
14
0
1
Order By: Relevance
“…Beyond information exchange, eliciting patient preferences is an integral part of the SDM process that few providers carry out because of their lack of training or lack of time during a patient visit ( 66 ). Options for improving SDM within LCS include patient and provider education ( 122 ), training program coordinators in SDM, and integrating mental health providers to conduct SDM tailored to the needs of patients with SMI and performed in mental health clinics ( 123 ). Furthermore, conducting SDM during a dedicated telephone visit with a dedicated decision counselor allows more time for SDM, with one study demonstrating similar patient satisfaction and low regret regardless of method of delivery ( 124 ).…”
Section: Resultsmentioning
confidence: 99%
“…Beyond information exchange, eliciting patient preferences is an integral part of the SDM process that few providers carry out because of their lack of training or lack of time during a patient visit ( 66 ). Options for improving SDM within LCS include patient and provider education ( 122 ), training program coordinators in SDM, and integrating mental health providers to conduct SDM tailored to the needs of patients with SMI and performed in mental health clinics ( 123 ). Furthermore, conducting SDM during a dedicated telephone visit with a dedicated decision counselor allows more time for SDM, with one study demonstrating similar patient satisfaction and low regret regardless of method of delivery ( 124 ).…”
Section: Resultsmentioning
confidence: 99%
“… 19 A regional LCS program integrating clinical navigation was later rolled out, whereby PCPs hand off potentially eligible individuals to designated clinician specialists who are responsible for verifying screening eligibility, providing education, conducting shared decision-making, and ordering baseline LDCT examinations. 20 For comparability and consistency across study sites, we considered receipt of a direct clinician referral for the baseline LDCT examination as being screened through a decentralized program and receipt of a referral through an LCS clinic or program for the baseline LDCT examination as being screened through a centralized program. Individuals at the health system in California were therefore classified as being screened through either a centralized or decentralized program, based on whether they were initially screened or not screened through the regional LCS program.…”
Section: Methodsmentioning
confidence: 99%
“…RCTs ( n = 4) performed appropriate randomization, had comparable groups at baseline, presented complete data outcomes, and had participants adhere to the assigned intervention; however, only one RCT reported on blinding the outcome assessor ( Emery et al , 2019 ) ( Supplementary Table 2S ). As for non-RCTs ( n = 11), only three studies reported that participants were representative of the target population ( Power and Wardle, 2015 ; Sakoda et al , 2020 ; Williams et al , 2021 ), and one study accounted for confounders ( Williams et al , 2021 ). Otherwise, all non-RCTs met the remaining MMAT criteria ( Supplementary Table 3S ).…”
Section: Resultsmentioning
confidence: 99%
“…Subjective and objective knowledge of LC were promoted in 12 studies using approaches, such as decision aids ( Lau et al , 2015 ; Mazzone et al , 2017 ; Housten et al , 2018 ); film and booklet ( Ruparel et al , 2019 ) and educational sessions ( Williams et al , 2021 ; Sakoda et al , 2020 ). Lau et al (2015) evaluated the effectiveness of a web-based decision aid ( www.shouldiscreen.com ) among 60 at-risk individuals and found that knowledge of risk factors, benefits and harms of screening, screening eligibility and percentage of benign lumps increased significantly 4 months post-test [pre-test: mean = 7.52/14, standard deviation (SD) = 1.89; post-test: mean = 10.93/14, SD = 2.19; p < 0.001].…”
Section: Resultsmentioning
confidence: 99%